Power quality improvement by using non-linear sliding mode controller with the dynamic voltage restorer - Mohammed, Ali Basim (2021)
The essential issue of the power system network is power quality. The bus voltage must be maintained as a sinusoidal waveform. Many disturbances affect the supply voltage, such as notching, transients, voltage sag/swell. The major power quality problems are voltage sag/swell and harmonics, which cause tripping or malfunctioning the equipment. The linear PID controller's output suffers from a high amplitude of error when the input signals are noisy. This thesis gives an effective solution to protect the sensitive loads from disturbances by utilizing the dynamic voltage restorer. It is defined as a controlled voltage source connected in series between the sensitive loads and the network through a series transformer to inject a proper voltage magnitude to keep the sensitive loads at a constant value. The two non-linear controllers employ a robust differentiator known as an approximate sliding mode differentiator (ACSMD) with a non-linear sliding variable named a terminal PID sliding variable (TPIDSV) or arctan PID sliding variable (ARTPIDSV). Simulation results were carried out by MATLAB/Simulink to investigate the performance of the proposed controllers. The performance improvement obtained from the proposed techniques upon comparison with the case study as a linear PID controller, the steady-state error 85%-99%, the total harmonic distortion 2%-51%, the voltage sag indices 85%-99% and the load voltage magnitude 0.2%-8.7% for voltage sag and 0.08%-2.9% for voltage swell in all cases. The results illustrated the DVR structure's ability to overcome the system's disturbances, maintaining the voltage magnitude of the sensitive loads at a constant value, minimizing the steady-state of error, and keeping the THD at an IEEE standard. The DVR system performance is evaluated by utilizing three types of voltage sag indices.